2013
DOI: 10.1111/phn.12071
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of an Urban Home‐Based Intervention Program on Asthma Outcomes in Children

Abstract: This multifaceted home-based intervention decreased asthma triggers and improved asthma outcomes in children, and improved the quality of life of their caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…Mattress covers were also used in 19 multicomponent intervention studies. [49][50][51][52]54,55,58,59,61,62,[65][66][67][68][69][70][71]74,76 In these studies no improvement was found for emergency department use (SOE: low), hospitalizations (SOE: high), or acute care visits (SOE: moderate). However, school absenteeism and missed activities decreased (SOE: low).…”
Section: Mattress Coversmentioning
confidence: 99%
See 2 more Smart Citations
“…Mattress covers were also used in 19 multicomponent intervention studies. [49][50][51][52]54,55,58,59,61,62,[65][66][67][68][69][70][71]74,76 In these studies no improvement was found for emergency department use (SOE: low), hospitalizations (SOE: high), or acute care visits (SOE: moderate). However, school absenteeism and missed activities decreased (SOE: low).…”
Section: Mattress Coversmentioning
confidence: 99%
“…There were no single-intervention studies examining mold removal. Six multicomponent studies examined mold removal [56][57][58][76][77][78] and found that asthma symptoms improved (SOE: low), but findings for other outcomes were inconclusive.…”
Section: Mold Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, these four studies do not demonstrate evidence of health benefits for clients from public health nurses using models or frameworks. No difference was found (SmithBattle et al, 2013), the change could not be attributed to the intervention (Tucker et al, 2011), additional elements were included than just the public health nursing intervention (Sweet et al, 2014), or the model applied was not adequately explained (Morgan et al, 2010). This review also highlights the lack of published literature over the last ten years which has attempted to measure the impact of public health nurses use of models or frameworks.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-five RCTs, two nonrandomized trials with concurrent controls, 88,89 and three pre-post studies [90][91][92] examined interventions that bundled multiple allergen-avoidance strategies. Six of the 30 studies included application of an acaricide to carpeting.…”
Section: Studies Of Multicomponent Interventionsmentioning
confidence: 99%